Strongyloidiasis mimics duodenal lymphoma in a patient with systemic lupus erythematosus and antiphospholipid syndrome: a case report - Ayoub Basham; Sanaz Soleimani; Atash Ab Parvar; Arash Rahimi; Ebrahim Evazi; Seyed Hamid Moosavy (Journal of Medical Case Reports)
Abstract Background Systemic lupus erythematosus is a multi-organ autoimmune disorder that is treated by immunosuppressive agents that weaken the immune defense against opportunistic pathogens and latent infections such as strongyloidiasis. Herein, we report the case of a 43-year-old woman known to have systemic lupus erythematosus who presented with gastrointestinal symptoms, edema, and bone pain 2 months after receiving immunosuppressive treatment. Case presentation A 43-year-old Iranian female known to have systemic lupus erythematosus and antiphospholipid syndrome presented with abdominal pain, nausea, vomiting, and generalized edema. She was on CellCept, prednisolone, and hydroxychloroquine. The vital signs were within the normal range. On physical examination, no rash was observed on the skin. There was only a mild tenderness in epigastric region. The results of blood analysis revealed hypochromic microcytic anemia, normal leukocyte count with mild eosinophilia. Liver enzymes as well as renal function tests were within the normal range. Stool examination was negative for trophozoites, ova, or cysts of parasites. Endoscopic findings included a generalized nodular appearance of duodenum with an infiltrative mucosa in the wall of duodenum, suggesting lymphoma. The pathology report determined the diagnosis of strongyloidiasis. Cap albendazole 400 mg was administered twice a day for 2 weeks. Abdominal pain was completely relieved 1 week after starting the treatment. The patient was eventually discharged after 10 days. Conclusion The significance of this case report is the necessity to send complete blood count and serologic assays to screen latent strongyloidiasis before receiving immunosuppressive agents in patients with systemic lupus erythematosus.